STOCK AND STOCK EXCHANGE AS A PART OF FINANCIAL INSTITUTIONS IN DEVELOPED COUNTRIES - Petrović, Vesna; Simić, Nataša; Aničić, Dušan (Journal of process management and new technologies, 2018)
The authors have tried to present the term, meaning and importance of stocks and stock exchange as a part of the financial system of developed countries. By observing the financial system growth, especially in financial institutions, it can be noticed that there are changes in relative positions of various types of financial agents in developed market industries. What determines financial markets, and by that the stocks and stock exchange is the permanent movement of financial instruments and neglecting the national market boundaries.